2007
DOI: 10.1371/journal.pgen.0030219
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism Misregulating p27 in Tumors Discovered in a Functional Genomic Screen

Abstract: The cyclin-dependent kinase inhibitor p27KIP1 is a tumor suppressor gene in mice, and loss of p27 protein is a negative prognostic indicator in human cancers. Unlike other tumor suppressors, the p27 gene is rarely mutated in tumors. Therefore misregulation of p27, rather than loss of the gene, is responsible for tumor-associated decreases in p27 protein levels. We performed a functional genomic screen in p27+/− mice to identify genes that regulate p27 during lymphomagenesis. This study demonstrated that decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Changes in the proliferative state of CTCL T cells have thus far been attributed to inactivation or loss of translation resulting from methylation of the tumor suppressors BCL7a (41), p15, and p16INK4 (42,43), which inhibit the retinoblastoma protein via interaction with cyclin D. However, deactivation of p16INK4 by bim-1 and ras oncogenes appears to occur primarily during latter stages of disease. In an attempt to further identify alterations in the regulation of CTCL neoplastic cell growth, we investigated potential changes in expression levels of another cyclin kinase-dependent inhibitor, p27Kip1 (44,45). Our studies indicate that in 11 out of 11 primary T cell samples obtained from patients with CTCL there was a reduction in p27Kip1 levels, consistent with a hyperproliferative state.…”
Section: Discussionmentioning
confidence: 95%
“…Changes in the proliferative state of CTCL T cells have thus far been attributed to inactivation or loss of translation resulting from methylation of the tumor suppressors BCL7a (41), p15, and p16INK4 (42,43), which inhibit the retinoblastoma protein via interaction with cyclin D. However, deactivation of p16INK4 by bim-1 and ras oncogenes appears to occur primarily during latter stages of disease. In an attempt to further identify alterations in the regulation of CTCL neoplastic cell growth, we investigated potential changes in expression levels of another cyclin kinase-dependent inhibitor, p27Kip1 (44,45). Our studies indicate that in 11 out of 11 primary T cell samples obtained from patients with CTCL there was a reduction in p27Kip1 levels, consistent with a hyperproliferative state.…”
Section: Discussionmentioning
confidence: 95%
“…Consistent with a tumor suppressor role for p27, loss of p27 in the nuclei of tumor cells is frequent in human tumors, and this is associated with high-grade tumors and poor prognosis (7,8). However, in contrast to conventional tumor suppressors such as p53 or Rb, loss of p27 expression most commonly occurs not through genetic mutations or epigenetic silencing, but rather via increased proteolytic degradation, relocalization in the cytoplasm, or transcriptional repression (2,8,9). p27 also has roles independent of its cyclin-CDK inhibitory function (2).…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, it has been shown that SKP2 and p27 levels exhibit a significant inverse relationship that correlates with melanoma progression (Li et al., 2004). Mutations in p27 are rare (Lee and Kim, 2009), suggesting that other molecular mechanisms might contribute to p27 loss such as regulation by microRNAs (Felicetti et al., 2008), altered cellular localization from the nucleus to the cytoplasm (Ahn et al., 2009; Garrett‐Engele et al., 2007), and enhanced degradation by SKP2 (Calvisi et al., 2009; Bhatt et al., 2007). Other data suggest that certain oncogenic properties of SKP2 in melanoma are not directly related to the cellular status of p27 (Hu and Aplin, 2008; Katagiri et al., 2006; Yokoi et al., 2003; Sumimoto et al., 2006).…”
Section: Introductionmentioning
confidence: 99%